Learnings From a Novel Virtual Care Planning Intervention Targeting Registered Practical Nurses in Long-Term Care Homes During COVID-19 - Connelly, Denise; Yous, Marie-Lee; Garnett, Anna; Hung, Lillian; Hay, Melissa; Furlan-Craievich, Cherie; Snelgrove, Shannon; Babcock, Melissa; Ripley, Jacqueline; Snobelen, Nancy; Hamilton, Pam; O’Connell, Maureen; et al. (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2025)
Introduction: The PIECES approach has been utilized for over 25 years across various Canadian healthcare settings, including long-term care (LTC). PIECES fosters a team-based, person-centred approach to addressing responsive behaviors—such as yelling and restlessness—often linked to unmet personal needs. Objective: This study aimed to explore, with implementation of the virtual version of PIECES: (a) the experiences of LTC staff, focusing on challenges, facilitators, and recommendations; and (b) resilience and interprofessional collaboration among LTC staff. Methods: A convergent mixed method approach used focus groups with registered practical nurses (RPNs), managers, PIECES-trained RPN champions and PIECES mentors to gather their experiences. Surveys at baseline and post-intervention assessed individual and workplace resilience, and team collaboration. Results: Themes identified through reflexive thematic analysis included increased team collaboration and efficacy to manage responsive behaviors through PIECES care planning. Formalized processes supported by leadership with input from family/care partners enhanced nurses’ ability to provide the needed care for responsive behaviors. Primary challenges to PIECES implementation were unfamiliarity with technology and staff shortage. Recommendations included embedding technology in usual care, ongoing support with referral process and continued virtual PIECES training. Standard outcome measures revealed reduced personal and workplace resilience, and team collaboration. Discussion and Conclusion: The RPN-led referral algorithm for the virtual PIECES approach invested the LTC staff together during the difficult COVID period and challenged their existing skills and knowledge of technology.